2019
DOI: 10.1111/codi.14538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activated carbon nanoparticles on lymph node harvest in patients with colorectal cancer

Abstract: Aim The aim was to examine the effect of activated carbon nanoparticles (ACNs) on lymph node retrieval in colorectal cancer (CRC) patients. Methods This prospective randomized study of 80 subjects was performed between March 2016 and December 2016. Eighty patients with CRC were randomly divided into two groups, the ACN group and a control group. The patients in the ACN group were subjected to 1 ml of ACN injection in the subserosa around the tumour before colectomy and D3 lymphadenectomy. The patients in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Thirteen studies had reported total and (or) average number of dissected LNs in the CNPs group and the control group, respectively ( Table 3). Eleven of 13 studies showed that the total (and /or) mean number of detected LNs per patient was significantly higher in the CNPs group than in the control group, 23,[26][27][28][29][30][31][32][33][34][35][36] illuminating the superiority of CNPs in tracing LNs. Seven studies recorded the numbers of harvested metastatic LNs, [26][27][28][30][31][32][33][34] wherein two studies found more metastatic LNs in CNPs group, while four studies showed no significant difference between the two groups.…”
Section: Ln Retrievalmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies had reported total and (or) average number of dissected LNs in the CNPs group and the control group, respectively ( Table 3). Eleven of 13 studies showed that the total (and /or) mean number of detected LNs per patient was significantly higher in the CNPs group than in the control group, 23,[26][27][28][29][30][31][32][33][34][35][36] illuminating the superiority of CNPs in tracing LNs. Seven studies recorded the numbers of harvested metastatic LNs, [26][27][28][30][31][32][33][34] wherein two studies found more metastatic LNs in CNPs group, while four studies showed no significant difference between the two groups.…”
Section: Ln Retrievalmentioning
confidence: 99%
“…Eleven of 13 studies showed that the total (and /or) mean number of detected LNs per patient was significantly higher in the CNPs group than in the control group, 23,[26][27][28][29][30][31][32][33][34][35][36] illuminating the superiority of CNPs in tracing LNs. Seven studies recorded the numbers of harvested metastatic LNs, [26][27][28][30][31][32][33][34] wherein two studies found more metastatic LNs in CNPs group, while four studies showed no significant difference between the two groups. Seven studies recorded the patients with metastatic LNs, 23,26,28,[31][32][33][34] three studies detected more LN-positive patients in the CNPs group than in the control group, while four studies showed no significant difference.…”
Section: Ln Retrievalmentioning
confidence: 99%
See 3 more Smart Citations